The Relationship Between Vehicle Safety Factors Toward Riding Safety Behaviours In MA Al Muddatsiriyah Students, Central Jakarta In 2020 - Shiffa Inayati, Ash (Health Safety Environment, 2020)
According to Land Transportation Statistics during of 2013-2017, the number of traffic accident has increased  average by 0,77 percent annually. However, material losses decreased on average by 4.21 percent annually. Traffic accidents is caused by human factors that lack awareness and poor knowledge of the drive. The purpose of research to determine the relationship between riding safety factors with riding safety behavior in MA Al Muddatsiriyah students in Central Jakarta. This research is quantitative study with cross- sectional research design. This study was conducted at MA Al Muddatsiriyah Global Islamic School Central Jakarta with sample size of 109 students June 2020. The independent variables this study are knowledges, attitudes, vehicle conditions, training participation and the role of peers. The analysis used this study is chi-square test. The results of study showed knowledge with p- value 0.920  (OR  10.29),  attitudes  with  p-value 0.383  (OR  0.663),  conditions vehicles with p-value 0.054 (OR 23.81), training participation with p-value 1,000 (OR 11.00),  role of peers p-value 1.000 (OR 10.50). The conclusion of this study showed that there was no relationship between knowledge, attitude, vehicle condition, training participation and the role of peers with driving safety behavior in MA Al Muddatsiriyah students in Central Jakarta.Keyword: Behavior, Riding Safety, Students, Knowledge, Attitude, Vehicle Condition, Training Participation, Peer Roles.